STATISTICAL ANALYSIS OF ELECTRODE-ELECTROLYTESEPARATOR TO IMPROVE EFFECTIVENESS OF SUPERCAPACITOR (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The supercapacitor is a booming technology whose popularity is increasing as the number of electric vehicles areincreasing. The supercapacitor is a technology which will be a supporting pillar for electric vehicles and hydrogenvehicles to take the market. Supercapacitors will reduce stress on the main energy storage device thereby increasingtheir life and bettering performance. In the supercapacitor electrode, electrolyte and separators are the main parts.The effect of electrode, electrolytes, and separators have been extensively studiedseparately in the past, but theircombined effect has not been studied. Each of the three parts has one important parameter which contributes themaximum in capacitance of supercapacitor. These parameters are taken into consideration and their individual andinteraction effect on capacitance of supercapacitor is being studied in this paper. A statistical model has been usedfor analysis. The generated statistical model has been validated at a few points and error is within 5%. Thisstatistical model can be utilized by researchers and manufacturers in due course.